Optimizing Self-Compacting Concrete through the Incorporation of Calcined Mud at 850°C - Rachida Mohamed Krachaï; Moulaï Abdellah Bouabdallah (Journal of Building Materials and Structures)
The quantity of mud increases annually at dam sites, thereby reducing their storage capacity. To extend the lifespan of these structures, dam dredging is an essential solution. However, the extraction of enormous amounts of mud through the dam's bottom outlets, which remain unused, currently poses an environmental problem.